2011
DOI: 10.3899/jrheum.110904
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Stress on the Development and Severity of Immune-Mediated Diseases

Abstract: Evidence that psychological stress can increase inflammation and worsen the course of immune-mediated inflammatory disease (IMID) is steadily accumulating. The majority of data supporting this hypothesis come from studies in patients with inflammatory bowel disease (IBD). While there is no evidence to suggest that stress is a primary cause of IBD, many, although not all, studies have found that patients with IBD experience increased stress and stressful life events before disease exacerbations. Further, the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 32 publications
0
30
0
1
Order By: Relevance
“…In particular, stress may increase intestinal permeability, potentially as a result of alterations in the cholinergic nervous system and mucosal mast cell function 98,99. Data revealing that psychological stress may increase inflammation and worsen the clinical course of immune-mediated inflammatory disease are also increasing 100. A recent study has shown that although short-term stress does not trigger exacerbation in UC, long-term perceived stress increases the risk of fare over a period of months to years 101.…”
Section: Lifestyle Exposuresmentioning
confidence: 99%
“…In particular, stress may increase intestinal permeability, potentially as a result of alterations in the cholinergic nervous system and mucosal mast cell function 98,99. Data revealing that psychological stress may increase inflammation and worsen the clinical course of immune-mediated inflammatory disease are also increasing 100. A recent study has shown that although short-term stress does not trigger exacerbation in UC, long-term perceived stress increases the risk of fare over a period of months to years 101.…”
Section: Lifestyle Exposuresmentioning
confidence: 99%
“…Threatening life experiences and chronic stress increase the likelihood of relapse in patients with quiescent IBD [8]. Various pathophysiological mechanisms have been suggested by which stress can affect the gastrointestinal immune and inflammatory responses [9,10]. To date, there is insufficient understanding of the role of stressful life events in large community cohorts of CD patients not limited specifically to periods of disease onset or exacerbation.…”
Section: Introductionmentioning
confidence: 97%
“…In previous cohort studies of comorbid CD and depression, depression was treated as a homogenous construct without regard to the varied symptoms of depression (3, 4, 17). It is possible that these earlier cohort studies of depression and CD may have demonstrated correlation because the somatic symptoms of depression may be more strongly linked to the mechanisms thought to underlie the depression-CD relationship (22). Another advantage of the present study was the use of CD activity level as a continuous variable at baseline instead of the more typical dichotomization which results in reduced power.…”
Section: Discussionmentioning
confidence: 99%